Hidden in Plain Sight: The Importance of Scale in Organizations’ Attention to Issues - Bansal, Pratima; Kim, Anna; Wood, Michael O. (Academy of Management Review, 2018)
The organizational attention literature has an epistemological bias, in that it explains how and why organizations notice issues. The ontological or real attributes of the issues are largely ignored, subordinated, or confounded with this epistemological orientation. In this article we argue that organizations sometimes miss issues, not only because of attentional failures but also because of the temporal and spatial scale of the underlying processes related to the issues. Some processes are of such large or small scale they escape organizational attention. We argue that large-scale processes, such as those related to climate change, require broad attentional extent, whereas small-scale processes, such as those related to local variations in poverty, require fine attentional grain. This work aims to shed light on the relatively underexplored question of why some issues are not noticed, with important implications for both theory and practice.